Analysis of the Effectiveness of Pop-Up Book Media on Science Learning in Elementary Schools - Maharani Zaniyati; Rohmani Rohmani (IJORER : International Journal of Recent Educational Research, 2024)
Objective: Science education in elementary schools provides basic scientific knowledge and skills and develops students' critical and creative thinking abilities. This study aims to analyze the effectiveness of using pop-up books as media in learning science in elementary schools. Method: In this study, researchers applied the Systematic Literature Review (SLR) method using the Google Scholar database. The literature search focused on the initial keyword "learning media," restricted from 2019 to 2024, resulting in 86,200 articles. Furthermore, with the addition of the keyword "pop-up book," 4,120 articles were found. Then, adding the last keyword, "science in elementary school," resulted in 318 articles. From this number, data selection and eligibility tests were carried out to obtain suitable articles until 11 appropriate articles were obtained and by the literature review's objectives. Results: Based on the study's results, it can be concluded that pop-up book media has proven effective in learning science in elementary schools. Novelty: For educators, engaging learning media in learning science is recommended to convey the learning material well and effectively, including pop-up books.